PERCEIVED EFFECTS OF CLIMATE CHANGE ON RICE PRODUCTION IN JAMAARE AND ITAS GADAU LGAs OF BAUCHI STATE, NIGERIA - Sintali, Z. A.; Murtala, N.; Bose, A. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the effect of climate change on rice production in Jama’are and Itas/Gadau LGAs of Bauchi State, Nigeria. Multistage sampling techniques was used to select 216 respondents from the study area. Data were collected using structured questionnaire and analyzed using both descriptive and inferential statistics. The result revealed that almost all (97%) of the respondents were male and 62.9% married with a mean age of 35years. The result also showed that the respondents had a mean household size and farm size of 6 persons and 1.6ha. The most severe perceived effects of climate change on rice production were loss of soil water, low yields, increased weed growth and low soil fertility with a mean score (=3.7), (=2.8), (=2.7) and (=2.7), respectively. The results of regression analysis revealed that farm size and farming experience were positive and significant (P< 0.01) influencing rice yield while access to credit was positive and significant (P<0.05). The major constraints faced by rice farmers were low capital, low yield of early maturing varieties (100%), frequent floods (100%), and high cost of fertilizer (100%). The study concluded that loss of soil water, low yield, increased weed growth and loss of soil fertility were some of the perceived effects of climate change in the study area. Based on the findings the respondents should promote and strengthen cooperative membership, Adequate and timely information on climate change should be provided by extension agents to enable rice farmers take adequate adaptation and mitigation measures.